CLOUD TECHNOLOGY AS A COMPONENT OF IT FOR SCHOOL - I.V. Plish (Kherson State University, 2013)
The article considers the problem of management of the quality of education in secondary schools. The main problem is to find and develop new ways and means to manage the quality of education that involve the using of cloud technologies.